Literature Review Pemanfaatan Sabut Kelapa dalam Pengelolaan Air Asam Tambang - Amila Sefti; Edy Nursanto; Rika Ernawati (Retii, 2023)
Acid Mine Drainage is one of the environmental problems most frequently faced by the mining industry. Acid mine drainage occurs when sulfide minerals such as pyrite (FeS2) and marcasite (FeS3) are exposed due to mining activities such as dismantling overburden and coal excavation, causing them to react with oxygen and water. Based on the literature review, there are several adsorbents used in the management of acid mine drainage to reduce heavy metals, one of which is coconut fiber. To reduce the impact of acid mine drainage, an effective and efficient management method is needed. An effective method for managing acid mine drainage is to reduce heavy metals using coconut fiber carbon impregnated with a solution of mercaptobenzothianol (MBT). The research results stated that the absorption of heavy metals for the optimum value in coconut fiber carbon impregnated with mercaptobenzothianol (MBT) was 99.93%, however this method was not efficient because it was quite expensive. The most efficient method is the acid mine drainage method using coconut fiber because it is economical and environmentally friendly.